Effectiveness of strategies and interventions aiming to assist the transition from student to newly qualified nurse: an update systematic review protocol. (February 2019) - Edwards, Deborah; Carrier, Judith; Hawker, Clare
Abstract : Review question/objective: The objective of this systematic review update is to evaluate recent available research on the effectiveness of strategies and interventions aiming to assist the transition from student to newly qualified nurse for job satisfaction, confidence, competence, knowledge, stress, anxiety, retention, turnover and costs.